In-vitro Antioxidant and Free Radical Scavenging Activity of A 50% Hydroethanolic Polyherbal Crude Extract - Sudhakar, Monisha; Perumal, Arthi Varadharaja; Rassappan, Ragavi; Sambamurthy, Sandhya; Kumar, Susmitha Senthil; Sundar, Swathi; Viswanathan, Varshini; Krishnan, Yogesh Leela (Asian Journal of Pharmaceutical Research and Development, 2020)
The multiple activities of the plant based medicinal preparations meant for varieties of inflammatory diseases offer enormous scope for combating the threat of diseases. The present study was designed to develop safer, effective and viable anti-inflammatory herbal combination to control oxidative stress related ailments as new alternatives to synthetic drugs. The synergistic potential of herbal combination of two medicinal plants was assessed through curative and preventive mode of treatment. Among the numerous traditional herbs, Gymnea sylvestre and Urgenia Indica is widely used for its traditional value. Free radicals induce numerous diseases by lipid peroxidation, and DNA damage. It has been reported that numerous plant extracts have antioxidant activities to scavenge free radicals. In the present study, the antioxidant properties of crude 50 % hydroethanolic polyherbal crude extract of Gymnea sylvestre and Urgenia Indica were studied in in-vitro models viz. radical scavenging activity by DPPH reduction Assay, Scavenging of SO, H2O2 and reducing power, DOT PLOT and FRAP assay. The extract was found to contain large amounts of phenolic compounds and flavonoids. 50% hydroethanolic polyherbal crude extract of Gymnea sylvestre and Urgenia Indica possessed significant antioxidant activity. These results suggest that synergistic activity of the crude extract has potential to develop a new functional dietary agent to treat chronic metabolic diseases, such as diabetes , hyperlipidemia and various inflammatory diseases.